Role of Smad3 and p38 Signalling in Cigarette Smoke-induced CFTR and BK dysfunction in Primary Human Bronchial Airway Epithelial Cells - Sailland, Juliette (Sci Rep, 2017)
Mucociliary clearance (MCC) is a major airway host defence system that is impaired in patients with smoking-associated chronic bronchitis. This dysfunction is partially related to a decrease of airway surface liquid (ASL) volume that is in part regulated by apically expressed cystic fibrosis transmembrane conductance regulator (CFTR) and large-conductance, Ca(2+)-activated, and voltage dependent K(+) (BK) channels. Here, data from human bronchial epithelial cells (HBEC) confirm that cigarette smoke not only downregulates CFTR activity but also inhibits BK channel function, thereby causing ASL depletion. Inhibition of signalling pathways involved in cigarette smoke-induced channel dysfunction reveals that CFTR activity is downregulated via Smad3 signalling whereas BK activity is decreased via the p38 cascade. In addition, pre-treatment with pirfenidone, a drug presently used to inhibit TGF-β signalling in idiopathic pulmonary fibrosis, ameliorated BK dysfunction and ASL volume loss. Taken together, our results highlight the importance of not only CFTR but also BK channel function in maintaining ASL homeostasis and emphasize the possibility that pirfenidone could be employed as a novel therapeutic regimen to help improve MCC in smoking-related chronic bronchitis.